LIBERTAÇÃO NA AMÉRICA LATINA: NOTAS ACERCA DA TEOLOGIA DA LIBERTAÇÃO (Razão e Fé, 2021)
The object of our study is the relationshipbetween theology and liberation. The issueof liberation is analyzed in the historical andsystematic view of Latin American theologyand its contributions in Latin America. Forthis purpose, we will examine the concepts ofliberation and integral development, liberationin Latin American theology, indicating pathsand perspectives for Latin American liberationtheology.